Evaluation of warning strategies for paraneoplastic neurological syndromes associated with PD-1/PD-L1 inhibitors - Ren, Zhuangzhuang; Liu, Yudan; Liu, Jianguo; Qi, Xiaokun; Qiu, Feng; Sun, Chenjing (Frontiers in Immunology, 2025)
BackgroundThe suppressive effects of immune checkpoint inhibitors (ICIs) on anti-tumor immunity have been well documented. However, ICIs can enhance immune responses and trigger autoimmune-related diseases by blocking PD-1 or PD-L1. The worst prognosis is observed in paraneoplastic neurological syndromes (PNS). This study aimed to evaluate the clinical characteristics of PD-1/PD-L1 inhibitor–related PNS and the prognostic impact of antibody subtypes, with the goal of enabling pre-treatment risk warning.MethodsThis was a retrospective descriptive study involving 224 patients with PD-1/PD-L1 inhibitor–related PNS from May 2015 to May 2025, including 8 patients who presented at our hospital and 216 patients reported in the literature. According to the July 2021 international consensus diagnostic framework for PNS, patients were stratified into risk-antibody (high-, intermediate-, and low-risk), unknown-risk antibody, and antibody-negative groups. Clinical features, primary tumor type, ICI regimen, autoantibody profile, treatments, and outcomes were analyzed. Risk-antibody subtypes were further explored.ResultsThere were 112 patients in the risk-antibody group (87 high-risk, 20 intermediate-risk, and 5 low-risk), 51 in the unknown-risk antibody group, and 61 in the antibody-negative group. The risk-antibody group showed a higher incidence of limbic encephalitis, subacute cerebellar degeneration, and subacute sensory neuronopathy. The prognosis was worse in the risk-antibody group, with a mortality rate of 29%, significantly higher than 17% in the unknown-risk group and 10% in the antibody-negative group (P = 0.012). Anti-Hu–positive patients were mainly diagnosed with limbic encephalitis, encephalomyelitis, and subacute cerebellar degeneration, with a mortality rate of 23%. Anti-Ma–positive patients primarily presented with encephalomyelitis, limbic encephalitis, and subacute cerebellar degeneration, with a mortality rate of 35%. Anti-Yo–positive patients were mainly associated with subacute cerebellar degeneration, with a mortality rate of 25%. The mortality rate among Anti-amphiphysin–positive patients was 33%. In contrast, 71% of Anti-NMDAR–positive patients had favorable outcomes.ConclusionAmong patients with PD-1/PD-L1 inhibitor–related PNS, those with risk-antibody positivity had worse prognoses, while patients with unknown-risk antibodies had outcomes similar to those with antibody negativity, suggesting that unknown-risk antibodies are not directly pathogenic or may elicit weaker immune responses. Pre-treatment screening for PNS-related antibodies is recommended, as it may facilitate early warning, identify high-risk patients, and help prevent autoimmune-related diseases caused by excessive immune modulation. After disease onset, efficient immunomodulatory treatment tailored to antibody subtypes may improve outcomes in risk-antibody–positive patients.